2017
DOI: 10.1002/ags3.12024
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for development of nonalcoholic fatty liver disease after pancreatoduodenectomy

Abstract: Considerable attention has been focused on nonalcoholic fatty liver disease (NAFLD) which occasionally develops after pancreatoduodenectomy (PD). The present study aimed to clarify the prevalence, sequential change in properties and risk factors for NAFLD development after PD. We enrolled 196 patients who underwent PD and a computed tomography (CT) scan 1 month, 6 months and 1 year after surgery. NAFLD was defined as a liver‐to‐spleen attenuation ratio on plain CT of <0.9. We compared various clinical factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Second, a recent study used the pancreatic digestive enzyme pancrelipase delayed-release supplement (Lipacreon, Mylan EPD GK) 1.2 g/day and reportedly significantly improved NAFLD after PD 4,21 ; however, other studies indicated that the prevalence of NAFLD was not significantly reduced, even in patients who received pancrelipase supplements. 6,22 Third, several patients in this study might have recovered from NAFLD even if they had not received pancreatic digestive enzyme; however, it was difficult to identify these patients. To demonstrate the effectiveness of high-dose pancreatic enzyme treatment with respect to improvement of NAFLD, another randomized controlled trial involving the application and lack of intervention for patients with NAFLD is necessary; the strength of our conclusions may have been limited by the study design.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Second, a recent study used the pancreatic digestive enzyme pancrelipase delayed-release supplement (Lipacreon, Mylan EPD GK) 1.2 g/day and reportedly significantly improved NAFLD after PD 4,21 ; however, other studies indicated that the prevalence of NAFLD was not significantly reduced, even in patients who received pancrelipase supplements. 6,22 Third, several patients in this study might have recovered from NAFLD even if they had not received pancreatic digestive enzyme; however, it was difficult to identify these patients. To demonstrate the effectiveness of high-dose pancreatic enzyme treatment with respect to improvement of NAFLD, another randomized controlled trial involving the application and lack of intervention for patients with NAFLD is necessary; the strength of our conclusions may have been limited by the study design.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, patients who underwent PD were scheduled for CT scans at 1, 3, 6, and 12 months after surgery. Fujii and colleagues 22 reported that several patients recovered from NAFLD spontaneously, while others exhibited progressive deterioration. A more detailed examination may therefore reveal the incidence of NAFLD to be higher than previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatoduodenectomy (PD) is the standard surgical treatment for periampullary and pancreatic head tumor lesions, including pancreatic and biliary malignant, premalignant, and benign neoplasms. Advances in surgical techniques, perioperative management, and adjuvant chemotherapy have reduced surgery-related morbidity and mortality [ 43 , 44 ]. With improved long-term survival rates, there has also been an increase in rates of long-term metabolic complications, including NAFLD.…”
Section: Nafld Following Pancreatoduodenectomymentioning
confidence: 99%
“…The attenuation values were the average of the four measurements in each segment of the liver and spleen, as previously described [43]. Fatty liver was diagnosed as liver-to-spleen ratios <0.9 [44]. These analyses were performed using the diagnostic software ImageJ Version 1.50 (National Institutes of Health, Bethesda, MD, USA) [39].…”
Section: Evaluation Of Visceral Fat Area and Hepatic Fat Contentmentioning
confidence: 99%